Keterbatasan Transparansi DPR Dan Dampaknya Terhadap Kinerja Legislasi : Analisis Partisipasi Publik Dalam Kasus UU Cipta Kerja - Syafiqa Nadhira Kusuma; Janter Panjaitan; Unggul Pamekas; Adhirajasa Shidqi Muhamad; Rafli Akbar Rafsanjani; Fidanzani Zulfadikhan Azhar; Kuswan Hadji (Lembaga Pengembangan Kinerja Dosen, 2025)
This article examines the limitation of transparency within the Indonesian House of Representatives (DPR) during the formulation of the Job Creation Act (Law No. 11 of 2020) and its implications for legislative performance and public participation. Transparency represents a fundamental requirement in a democratic legal system as it ensures accountability, public oversight, and the legitimacy of legal products. However, the legislative process of the Job Creation Act demonstrated significant procedural issues, including inconsistent draft versions, restricted access to essential documents, accelerated deliberation, and the marginalization of meaningful public participation. This study highlights how these limitations hinder the public’s constitutional rights, weaken legislative oversight, and create asymmetrical power relations that enable elite dominance in policymaking. The lack of transparency also led to procedural defects acknowledged by the Constitutional Court, reflecting a systemic decline in democratic legislative practices. Using a normative juridical method supported by legislative analysis and doctrinal studies, this paper argues that the absence of transparency not only reduces the quality of participation but also erodes the legitimacy and accountability of the DPR. The findings emphasize the urgent need for open access to legislative documents, inclusive public consultation, and strengthened accountability mechanisms to ensure democratic and lawful policy making.